Toddlers' Oral Health Related Quality of Life (OHRQoL) by Gender - Yani, Ristya Widi Endah; Prayitno, Hadi; Lestari, Indah; Ratnaningsih, Tri; Wijayanti, Lumastari Ajeng (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Toddlers’ caries prevalence is influenced by some factors such as social status, economic status, parents' educational background, and dietary pattern. Caries in toddlers have a negative impact on their quality of life. The objectives of this research are to analyze the differences in Oral Health Related Quality of Life (OHRQoL) by gender. Analytical observational research design with a cross-sectional approach. The research population is toddlers with their parents in the Silo II Health Centre work area. The sample is 3-5 years toddlers as many as 71 respondents. The variables studied were Oral Health Related Quality of Life (OHRQoL) of male and female toddlers with the Ecohis index measuring instrument. The research data were tabulated and analyzed using the Mann-Whitney test. The majority of respondents were female toddlers (57.7%), the age range of 60-71 months (57.7%), parents’ last education is elementary school (49.3%), with an income of less than 2 million per month (59.1%). There are no differences in Oral Health Related Quality of Life of male and female toddlers with a p-value of 0.404. There are no differences in Oral Health Related Quality of Life between female and male toddlers